2021
DOI: 10.1111/aab.12720
|View full text |Cite
|
Sign up to set email alerts
|

Cecidophyopsis mites and blackcurrant reversion virus on Ribes hosts: Current scientific progress and knowledge gaps

Abstract: The production of Ribes (Rosaceae) in temperate regions in Europe, Asia and New Zealand is severely constrained by damages of Cecidophyopsis mites (Acari: Eriophyidae) and blackcurrant reversion virus (BRV) (Nepovirus, Secoviridae). The infestation of Ribes plants with Cecidophyopsis mites and BRV infection is a complex tripartite system. This paper reviews scientific progress and knowledge gaps on the Cecidophyopsis‐BRV‐Ribes complex emphasising Cecidophyopsis mites as a pest and natural vector of BRV, BRV as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 117 publications
(291 reference statements)
0
4
0
Order By: Relevance
“…BRV is one of the most serious pathogens in blackcurrant plantations; its control is complicated and the consequences are economically damaging [28]. Heterogenic infection of BRV in the same host plant of field-grown cv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BRV is one of the most serious pathogens in blackcurrant plantations; its control is complicated and the consequences are economically damaging [28]. Heterogenic infection of BRV in the same host plant of field-grown cv.…”
Section: Discussionmentioning
confidence: 99%
“…Under controlled conditions, transmission assays showed that 3 h of mite feeding on blackcurrant seedlings was sufficient for virus transmission [21]. However, previous studies have shown that using the gall mite infection method in vitro had difficulties in controlling both the infection pressure and the influence of environmental conditions on the spread of mites and BRV [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…RNA1 encodes five proteins: N-terminus protease co-factor, followed by nucleotide-binding protein or helicase, putative VPg, cysteine protease (CysPro), and RNA-dependent RNA polymerase [ 9 ]. Different genes of the virus are recognized as plant virus avirulence ( Avr ) factors in the viral Avr-R system [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…BRV is a small (approximately 29 nm in diameter) icosahedral Nepovirus [ 6 ]. BRD etiology has been studied very sparsely; however, the positive-sense single-stranded RNAs of BRV have been characterized [ 7 , 8 , 9 ]. BRV is bipartite and has three isometric virion components: M with RNA1 (7711 bp), B with RNA2 (4600 bp), and T with satRNA (1432 bp), with all of them containing a single open reading frame (ORF).…”
Section: Introductionmentioning
confidence: 99%